Pemanfaatan Media Sosial dalam Pengenalan Bibit Kopi Berkualitas dari UB Forest - Utari, Dwi Yanti Retno; Nintia, Sri Wahyuni; Wijayanti, Fifilia Nindi; Siwi, Dhea Alda Rahmadani Putri (Neolectura, 2024)
This Community Service (PKM) program aims to introduce quality coffee seeds from UB Forest to the coffee farming community in Malang Raya through the use of social media. Documentation and dissemination of information is carried out using the social media platform Facebook to reach a wider audience. The method of implementing this program includes preparation, implementation and evaluation stages. In the preparation stage, the PKM team conducted site surveys and initial discussions to understand field conditions and prepare relevant content. The implementation stage involves creating a Facebook account